Film, Fashion, and the Modern Woman: Western Cultural Influences in Hungary in the 1930s - Fejes, Katalin (Stan Rzeczy, 2021)
This paper takes a novel approach to exploring the relationship between fashion salons and sound films in making the image of the modern woman in the 1930s. In this period, liberal cultural tendencies contradicted the increasingly authoritarian political trends in Central Europe. In Hungary, sound films transformed the fashion industry, and fashion salons were quick to respond by creating new clothing for the modern women. This paper investigates the figure of the modern woman as it appeared in newspapers, fashion magazines, and sound films. The type of independent, purposeful woman shown in the films, with her confidence, fashionable costumes, and romance, became an ideal for young women. As dressmakers for film actresses, fashion salons played a significant role in conveying the Western style of dress. They influenced the collective representation of a generation through the representation of film actresses. However, the popularity of the “modern woman” turned out to be temporary in society, which was increasingly subjected to authoritarian policies in the shadow of European fascism. After 1938, the film industry was transformed; film directors and actors or actresses of Jewish origin were forbidden to continue their profession. Curiously, the discriminatory legislation did not touch the fashion salons, which continued to exist and started to produce traditional clothes. This paper puts these contradicting processes in context.